Alkali cellulose material, viscose, and method for producing viscose

By optimizing the production process with regenerated cellulose and controlled mercerization and sulfurization, viscose with enhanced solubility and quality is achieved, addressing the inefficiencies of traditional methods.

JP2024178623APending Publication Date: 2024-12-25RENGO CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023096900
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2024-12-25

AI Technical Summary

Technical Problem

Existing methods for producing viscose from cellulose result in high costs, poor dispersion, and low-quality products due to unreacted fibers and low solubility, leading to inferior molded articles.

Method used

Using regenerated cellulose as a raw material, the process involves controlled mercerization with minimal alkaline solution and optimized sulfurization with carbon disulfide to achieve high cellulose and alkali concentrations, ensuring uniform mixing and reaction conditions.

Benefits of technology

The method produces viscose with improved solubility and physical properties suitable for forming cellulose molded products, reducing environmental impact and operational costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178623000003
    Figure 2024178623000003
  • Figure 2024178623000001
    Figure 2024178623000001
  • Figure 2024178623000002
    Figure 2024178623000002
Patent Text Reader

Abstract

To provide an alkali cellulose material that yields viscose having physical properties suitable for use as a starting material for the molding of a variety of cellulose molded objects by utilizing recycled cellulose as the starting material.SOLUTION: The present invention provides an alkali cellulose material which is used as an intermediate material for producing viscose through sulfidization with carbon disulfide, the material containing recycled cellulose, an alkali, and water, and having a cellulose concentration of 27-40 mass% and an alkali concentration of 8-20 mass%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an alkali cellulose material which is an intermediate material for producing viscose, and in particular to an alkali cellulose material which uses regenerated cellulose as a raw material. [Background technology]

[0002] When manufacturing cellulose products such as cellophane, rayon, and beads, by-products such as scraps and off-standard products are generated. However, since cellulose does not have thermoplasticity and is insoluble in general-purpose solvents, using cellulose products as raw materials to prepare a cellulose solution such as viscose for reuse requires complicated work steps and high costs.

[0003] Viscose is usually prepared by first coarsely crushing the raw material dissolving pulp sheet and soaking it in a large amount of alkaline aqueous solution to turn it into alkaline cellulose (mercerization), squeezing it to remove excess alkaline aqueous solution, crushing it, reacting it with carbon disulfide to convert it into cellulose xanthate (sulfurization), and dissolving it in an alkaline aqueous solution.

[0004] Non-Patent Document 1 describes a method for producing viscose from wood pulp as a raw material by uniformly spraying a small amount of concentrated caustic soda solution onto the pulp in order to omit squeezing in order to reduce the amount of alkaline aqueous solution used (non-squeezing method).

[0005] Patent Document 1 describes the preparation of alkali cellulose by using recycled artificial cellulose-based raw materials as the raw material, immersing the raw materials in an alkaline aqueous solution, and then squeezing the raw materials, thereby carrying out sulfurization and dissolution. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Special Publication No. 2018-505973 [Non-patent literature]

[0007] [Non-Patent Document 1] Tadashi Maki, "Part 1: Experiments on the production of viscose without pressure," Journal of Sen-i-Gakkaishi, Vol. 2, No. 2, pp. 79-81, 1946 Summary of the Invention [Problem to be solved by the invention]

[0008] However, the viscose produced by the method of Non-Patent Document 1 has a problem in that a large amount of unreacted fibers remain, and the dispersed and dissolved state is poor.

[0009] In addition, when the alkali cellulose of Patent Document 1 is sulfurized and dissolved, viscose containing a large amount of undissolved matter is produced due to the low solubility of cellulose, which has the problem of poor filterability and poor practicality because only molded products with low strength properties can be obtained.

[0010] The present invention solves the above-mentioned problems, and its object is to provide an alkali cellulose material that can be used to obtain viscose using regenerated cellulose as a raw material, the viscose having physical properties suitable for use as a raw material for molding various cellulose molded products. [Means for solving the problem]

[0011] The present invention provides the following aspects. [Embodiment 1] An alkali cellulose material containing regenerated cellulose, an alkali, and water, which is used to produce viscose by sulfurization with carbon disulfide, the alkali cellulose material having a cellulose concentration of 27 to 40 mass% and an alkali concentration of 8 to 20 mass%.

[0012] [Aspect 2] The alkali cellulose material of aspect 1, wherein the cellulose component does not include native cellulose.

[0013] [Aspect 3] The alkali cellulose material of aspect 1 or 2, wherein the cellulose component comprises regenerated cellulose.

[0014] [Aspect 4] The alkali cellulose material of any one of Aspects 1 to 3, wherein the viscose has a cellulose concentration of 5% by mass or more.

[0015] [Aspect 5] The alkali cellulose material of any one of aspects 1 to 4, wherein the viscose has a clogging degree of 6,000 or less.

[0016] [Embodiment 6] A mixed alkali cellulose material comprising the alkali cellulose material of any one of embodiments 1 to 5 and an alkali cellulose material for the same use produced from a cellulose material other than regenerated cellulose.

[0017] [Embodiment 7] A sulfide of an alkali cellulose material containing regenerated cellulose, an alkali and water, and having a cellulose concentration of 27 to 40% by mass and an alkali concentration of 8 to 20% by mass, with carbon disulfide.

[0018] [Embodiment 8] A mixed sulfide of an alkali cellulose material with carbon disulfide, comprising the sulfide of the alkali cellulose material of embodiment 7 with carbon disulfide and the sulfide of an alkali cellulose material for the same use produced from a cellulose material other than regenerated cellulose with carbon disulfide.

[0019] [Embodiment 9] Viscose comprising regenerated cellulose, an alkali and water, and comprising a sulfide, with carbon disulfide, of an alkali cellulose material having a cellulose concentration of 27 to 40% by mass and an alkali concentration of 8 to 20% by mass.

[0020] [Embodiment 10] A mixed viscose comprising the viscose of embodiment 9 and a viscose produced from a cellulose material other than regenerated cellulose.

[0021] [Embodiment 11] A method for producing viscose, comprising sulfurizing an alkali cellulose material containing regenerated cellulose, an alkali, and water, and having a cellulose concentration of 27 to 40 mass% and an alkali concentration of 8 to 20 mass%, with carbon disulfide. Effect of the Invention

[0022] According to the present invention, there is provided an alkali cellulose material which can be used to obtain viscose having physical properties suitable for use as a raw material for forming various cellulose molded products by using regenerated cellulose as a raw material. According to the present invention, there is provided viscose having physical properties suitable for use as a raw material for forming various cellulose molded products by using this alkali cellulose material as an intermediate material. Furthermore, according to the present invention, there is provided a method for producing viscose having physical properties suitable for use as a raw material for forming various cellulose molded products by using regenerated cellulose as a raw material. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1 is a schematic diagram of a graph in which characteristic values ​​of viscose for calculating the degree of clogging are plotted. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, the embodiments of the present invention will be described in detail, but the scope of the present invention is not limited to the embodiments described here, and various modifications can be made without departing from the spirit of the present invention. In addition, when multiple upper and lower limit values ​​are described for a specific parameter, any upper and lower limit values ​​can be combined to form a suitable numerical range.

[0025] <Regenerated cellulose> The regenerated cellulose used as a raw material is mainly cellulose obtained by liquefying natural cellulose by the conventionally known viscose method or cuprammonium method, and then solidifying and molding it into a predetermined shape. Regenerated cellulose includes cellulose molded products, cellulose products produced by cutting cellulose molded products, and by-products produced when manufacturing cellulose molded products. They may be pulverized to improve reaction efficiency. Specific examples of regenerated cellulose include scraps, non-standard products, defective products, and waste cellulose products generated when manufacturing cellulose molded products such as cellophane, rayon, and beads. Furthermore, regenerated cellulose can be reused as a raw material instead of natural cellulose.

[0026] <Natural cellulose> The natural cellulose used as the raw material for viscose is not particularly limited, and examples thereof include pulp made from biomass such as wood, cotton, straw, bamboo, hemp, jute, and kenaf. The manufacturing method is also not particularly limited, and may be a mechanical method, a chemical method, or a method that combines the two. In terms of pulp quality, highly refined dissolving pulp, which is the main raw material for paper pulp, artificial fiber, cellophane, etc., is preferred.

[0027] <Alkaline cellulose material> Regenerated cellulose is reacted with an aqueous alkali solution to convert the cellulose contained therein into alkali cellulose. This process is generally called mercerization. The mixture after mercerization, which contains regenerated cellulose, alkali, and water, is called alkali cellulose material. The alkali cellulose material may be in the form of a solution, a dispersion containing insoluble matter, or a solid. Mercerization causes the cellulose to swell, improving the reaction efficiency when sulfurizing the alkali cellulose. As the alkali, strong alkaline compounds such as sodium hydroxide, lithium hydroxide, and potassium hydroxide can be used.

[0028] The mercerization process is generally carried out by immersing the cellulose material in a large amount of an aqueous alkaline solution, followed by squeezing to remove the excess aqueous alkaline solution. In contrast, in the present invention, the minimum amount of concentrated aqueous alkaline solution required for sulfurization and dissolution of the regenerated cellulose is added to the regenerated cellulose in advance to carry out mercerization. Depending on the state of the regenerated cellulose, a means such as spraying may be used to add the solution uniformly. Since an excessive amount of aqueous alkaline solution is not added, a dehydration step such as squeezing is unnecessary and is not carried out.

[0029] When regenerated cellulose is immersed in an alkaline aqueous solution, it absorbs a large amount of water and swells strongly, making it difficult to increase the cellulose concentration to an appropriate level by the usual dehydration method such as squeezing.

[0030] The amount of the aqueous alkaline solution added is adjusted according to the moisture content of the regenerated cellulose used as a raw material, but is adjusted so that the alkali concentration in the mixture of the regenerated cellulose and the aqueous alkaline solution is 8 to 20 mass%, preferably 9 to 18 mass%, and more preferably 10 to 16 mass%. The cellulose concentration in the mixture is adjusted to 27 to 40 mass%, preferably 29 to 38 mass%, and more preferably 30 to 36 mass%. By adjusting the alkali concentration and cellulose concentration in the mixture to within the above ranges, the physical properties of the resulting viscose become suitable as a raw material for forming cellulose molded products.

[0031] Next, the aqueous alkali solution and the regenerated cellulose are mixed and stirred to proceed with mercerization. For mixing and stirring at this time, a stirring device suitable for mixing a small amount of the aqueous alkali solution with the solid regenerated cellulose is selected. The stirring device has a stirring tank and is preferably equipped with a temperature control jacket around the stirring tank that can control the temperature. In order to precisely control the reaction temperature, it is preferable to use a device equipped with a low-speed blade that uniforms the temperature of the mixture by stirring the entire inside of the stirring tank during the reaction in mercerization. The shape of the low-speed blade includes anchor blades, ribbon anchor blades, helical ribbon blades, gate blades, paddle blades, etc., among which anchor blades and ribbon anchor blades are more preferable. Furthermore, in order to improve the stirring efficiency, the stirring shaft may be made oblique, horizontal, or eccentric, and a baffle plate may be provided in the stirring tank or the stirring tank itself may be rotated.

[0032] The mercerization of regenerated cellulose is carried out at a temperature of -20 to 50°C, preferably 0 to 40°C, and more preferably 10 to 30°C. If the temperature during mercerization is less than -20°C, labor and energy are required to maintain the liquid temperature at a low temperature, and if it exceeds 50°C, labor and time are required to cool it to a temperature suitable for sulfurization. The reaction time of mercerization is usually in the range of 0.5 to 120 hours, preferably 1 to 72 hours, and more preferably 2 to 48 hours. If the reaction time of mercerization is too short, penetration is insufficient and the reaction does not progress to the center, resulting in an increase in undissolved matter, but if the reaction time is too long, a decrease in the degree of polymerization occurs. In addition, since this decrease in the degree of polymerization occurs due to oxidation with oxygen in the air, mercerization may be carried out under reduced pressure or by replacing the air with nitrogen gas, hydrogen gas, or the like.

[0033] The alkali cellulose material of the present invention can be used by mixing with an alkali cellulose material prepared by a conventional method from a cellulose material other than regenerated cellulose. The alkali cellulose material to be mixed with the alkali cellulose material of the present invention is preferably used for the purpose of producing viscose by sulfurization with carbon disulfide. Examples of cellulose materials other than regenerated cellulose include natural cellulose such as dissolving pulp.

[0034] In this case, the content of regenerated cellulose in the mixed alkali cellulose material is 1 to 99% by mass, preferably 2 to 50% by mass, more preferably 3 to 20% by mass, based on the cellulose component. By increasing the content of the regenerated cellulose as much as possible, the recycling rate of the regenerated cellulose can be improved, and the effect of reducing the environmental load can be enhanced.

[0035] The alkali cellulose material of the present invention is contacted with carbon disulfide to react and convert it into cellulose xanthate. This process is generally called sulfurization. The sulfurization can be carried out by adding carbon disulfide to the alkali cellulose material after mercerization, mixing and stirring it. It is also possible to mix cellulose, an aqueous alkali solution, and carbon disulfide at once to carry out mercerization and sulfurization simultaneously.

[0036] In the mixture containing regenerated cellulose, an aqueous alkali solution, and carbon disulfide, the cellulose concentration and the concentration of the alkali compound are diluted with carbon disulfide added after mercerization unless further adjustment is required. The amount of carbon disulfide added in the mixture is adjusted to 5 to 60% by mass, preferably 10 to 50% by mass, and more preferably 15 to 40% by mass, based on the mass of cellulose. If the amount of carbon disulfide added is less than 5% by mass, the reaction with the alkali cellulose becomes insufficient, and if it exceeds 60% by mass, side reactions of carbon disulfide increase or unreacted carbon disulfide remains, which may reduce safety.

[0037] During sulfurization, the temperature of the mixture is made uniform by stirring the entire inside of the stirring tank. In sulfurization, since the alkali cellulose is a solid while the carbon disulfide exists as a liquid or gas, it is preferable to use a stirring device equipped with a low-speed blade that rotates along the wall of the stirring tank to homogenize the mixture, and equipped with a temperature-regulating jacket, as in mercerization.

[0038] The sulfurization of the alkali cellulose is carried out at a temperature of 0 to 50°C, preferably 5 to 40°C, and more preferably 10 to 30°C. If the temperature during sulfurization is less than 0°C, labor and energy are required to maintain the liquid temperature at a low temperature, and if it exceeds 50°C, the degree of polymerization of the cellulose is likely to decrease and the risk of fire increases. The reaction time for the sulfurization is set so that carbon disulfide is sufficiently permeated throughout the alkali cellulose, and is usually in the range of 30 minutes to 12 hours, preferably 1 to 9 hours, and more preferably 2 to 6 hours.

[0039] The obtained sulfide is dissolved at a temperature of 0 to 40°C, preferably 5 to 35°C, and more preferably 10 to 30°C. If the temperature during dissolution is less than 0°C, labor and energy are required to maintain the liquid temperature at a low temperature, and if it exceeds 40°C, the solubility of cellulose is likely to decrease. The dissolution time is set so that the clogging degree reaches a desired value and is completed, and depends on the conditions such as stirring, but is usually in the range of 2 minutes to 48 hours, preferably 4 minutes to 36 hours, and more preferably 5 minutes to 24 hours. At this time, dissolution can be performed in a short time, especially when high-speed impellers are used in combination. The shape of the high-speed impeller includes dispersing impellers, turbine impellers, propeller impellers, paddle impellers, rotor-stators, etc., and among them, dispersing impellers are preferable.

[0040] The carbon disulfide sulfide of the alkali cellulose material of the present invention can be used to produce viscose by dissolving it in an alkaline aqueous solution, or can be mixed with the carbon disulfide sulfide of an alkali cellulose material prepared by a conventional method from a cellulose material other than regenerated cellulose. Examples of cellulose materials other than regenerated cellulose include natural cellulose, and in addition to pulp made from biomass such as wood, cotton, straw, bamboo, hemp, jute, and kenaf, waste paper, paper powder, etc. can also be used, with pulp made from wood being preferred.

[0041] In this case, the content of regenerated cellulose in the sulfide of the mixed alkali cellulose material with carbon disulfide is 1 to 99% by mass, preferably 2 to 50% by mass, more preferably 3 to 20% by mass, based on the cellulose component. By increasing the content of the regenerated cellulose as much as possible, the recycling rate of the regenerated cellulose can be improved, and the effect of reducing the environmental load can be enhanced.

[0042] <Viscose> The viscose of the present invention obtained after completion of sulfurization and dissolution has the same physical properties as viscose, such as viscose, which is a raw material for forming various cellulose molded products. The viscose of the present invention has a clogging degree of 6,000 or less, preferably 4,000 or less, more preferably 2,000 or less. The smaller the clogging degree, the more excellent the solubility of the cellulose xanthate in the sulfide. The method for calculating the clogging degree is shown below.

[0043] (Clogging degree) Viscose is filtered at 23°C under a pressure of 0.04 MPa using a filter cloth made of five layers of cotton, and the mass of the filtrate V (g) is measured over time. After a certain time has passed, the filtration time t (min) and the inverse of the filtration rate t / V are plotted, and the degree of clogging is calculated from the slope of the resulting line (k / 2) according to the following formula. Figure 1 is a schematic diagram of a graph on which the measured characteristic values ​​of viscose are plotted. Clogging degree = 100,000 x k

[0044] The viscose of the present invention has a cellulose concentration of 5% by mass or more, preferably 6 to 12% by mass, and more preferably 8 to 10% by mass. Such a cellulose concentration is at the same level as that of viscose, which is a raw material for forming various cellulose molded products. If the cellulose concentration of the viscose is high, the viscosity becomes too high, and if it is low, the strength of the cellulose molded product becomes insufficient and the amount of chemicals such as acid used increases, which reduces the economic efficiency. The method for measuring the cellulose concentration is shown below.

[0045] (Cellulose concentration) The viscose is thinly spread on a pre-weighed glass plate using a Baker-type applicator (SA-201, manufactured by Tester Sangyo Co., Ltd.), the mass is measured, and the mass of the viscose is calculated. The plate is then left to stand in a constant temperature dryer at 70°C for 40 minutes, and each plate is immersed in a 10% by mass aqueous solution of ammonium chloride for 30 minutes to peel off the solidified viscose from the plate. It is then washed with distilled water, dried in a hot air dryer at 105°C, the mass is measured, and the cellulose concentration of the viscose is calculated using the following formula. Cellulose concentration = {mass after drying / (mass of viscose)} x 100

[0046] The viscose of the present invention has an alkali concentration of 2% by mass or more, preferably 4 to 12% by mass, and more preferably 5 to 10% by mass. Such an alkali concentration is at the same level as that of viscose, which is a raw material for forming various cellulose molded products. If the alkali concentration of the viscose is high, the amount of acid required for neutralization increases, and if it is low, the solubility decreases.

[0047] The viscose of the present invention can be easily solidified by being poured into a salt solution, a dilute acid such as sulfuric acid or hydrochloric acid, an organic solvent, or by being heated, and can be regenerated with an acid to give shaped products such as cellophane, rayon, beads, etc. When a dilute acid is used for the solidification, the solidification and regeneration proceed simultaneously.

[0048] The viscose of the present invention can be used in combination with viscose prepared by a conventional method from a cellulose material other than regenerated cellulose, such as natural cellulose, for example dissolving pulp.

[0049] In this case, the content of regenerated cellulose in the mixed viscose is 1 to 99% by mass, preferably 2 to 50% by mass, and more preferably 3 to 20% by mass, based on the cellulose component. By increasing the content of the regenerated cellulose as much as possible, the recycling rate of the regenerated cellulose can be improved, and the effect of reducing the environmental load can be enhanced. EXAMPLES

[0050] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited thereto. The unit "parts" in the examples is a unit based on mass.

[0051] <Example 1> To prepare a regenerated cellulose sample, cellophane ("PT #300" (product name) manufactured by Rengo Co., Ltd.) was mechanically crushed, passed through a round mesh with a diameter of 1 mmΦ, and washed with water to remove any attached softener (glycerin) to prepare a wet product (cellulose content: 43% by mass).

[0052] 100 parts of the regenerated cellulose sample and 36 parts of 40% by mass aqueous sodium hydroxide solution were placed in the stirring tank of a stirring device and mixed using a low-speed stirrer equipped with a paddle blade (Three-One Motor BL-600, manufactured by Shinto Scientific Co., Ltd.). While stirring this mixture, mercerization was carried out at room temperature of about 20°C to obtain alkali cellulose. The obtained alkali cellulose contained 32% by mass of cellulose and 11% by mass of sodium hydroxide.

[0053] Carbon disulfide was added to this alkali cellulose in an amount of 35% by mass per cellulose mass, and sulfurization was carried out for 4 hours while stirring at 30 rpm using the low-speed stirrer. Aqueous sodium hydroxide solution was added to the obtained sulfide, and the mixture was dissolved while stirring at 600 rpm at room temperature for 19 hours to obtain viscose. The obtained viscose contained 9.8% by mass of cellulose and 6.0% by mass of sodium hydroxide.

[0054] After completion of the sulfurization and dissolution, the viscosity and clogging degree of the obtained viscose were measured. The solubility of cellulose was evaluated based on the clogging degree. The results are shown in Table 1.

[0055] (viscosity) The temperature of the viscose was adjusted to 20° C., and the viscosity was measured using a Brookfield viscometer (No. 5 rotor, 20 rpm).

[0056] (Solubility) The evaluation criteria for solubility were as follows:

[0057] ◎(Excellent) Clogging level: 2,000 or less ○(Good) Clogging degree: 6,000 or less × (Poor) Clogging level: Over 6,000

[0058] <Example 2> Viscose was obtained in the same manner as in Example 1, except that the sulfide obtained by adding 25% by mass of carbon disulfide per mass of cellulose to the alkali cellulose prepared in Example 1 was dissolved for 10 minutes while stirring at 5,000 rpm at room temperature using a high-speed stirrer equipped with a dispersing blade ("Labo-lution" (trade name) manufactured by Primix Corporation). The obtained viscose contained 9.6% by mass of cellulose and 6.1% by mass of sodium hydroxide.

[0059] <Comparative Example 1> 100 parts of the regenerated cellulose sample prepared in Example 1 was immersed in 1000 parts of 18% by weight aqueous sodium hydroxide solution at 50°C for 1.5 hours to perform mercerization, and then dehydrated at 3,000 rpm using a centrifuge HF110F (trade name, manufactured by Kokusan Co., Ltd.) until the discharge of the solution stopped, to obtain alkali cellulose. The obtained alkali cellulose contains 22% by weight of cellulose and 16% by weight of sodium hydroxide.

[0060] Except for using this alkali cellulose, viscose was obtained in the same manner as in Example 1. The obtained viscose contained 8.2% by mass of cellulose and 6.1% by mass of sodium hydroxide.

[0061] The viscosity and clogging degree of the obtained viscose were measured in the same manner as in Example 1. The solubility of cellulose was evaluated based on the clogging degree. The results are shown in Table 1.

[0062] [Table 1]

[0063] As in Comparative Example 1, when cellophane, which is regenerated cellulose, is dissolved according to a general viscose manufacturing method, the solubility is low. The reason is that cellophane swells significantly in an alkaline aqueous solution, is not sufficiently dehydrated, and the cellulose concentration of the alkali cellulose is low (25 mass% or less). In other words, when the alkali cellulose is not sufficiently dehydrated, side reactions increase during sulfurization, and the conversion rate to cellulose xanthate decreases, which is thought to result in a decrease in solubility.

[0064] In Examples 1 and 2, although there were differences in the amount of carbon disulfide added and the stirring conditions during dissolution, alkali cellulose with a high cellulose concentration of 32% by mass could be prepared by adding a small amount of the minimum necessary concentrated alkaline aqueous solution to the regenerated cellulose and mixing them uniformly, instead of soaking the regenerated cellulose in a large amount of alkaline aqueous solution and dehydrating it. As a result, a viscose with excellent cellulose solubility was obtained.

[0065] In Non-Patent Document 1, which uses pulp as the raw material, filtration of viscose is more difficult than with the conventional method (the filtration time for 300 g of viscose is 177.4 seconds with the conventional method and 320 seconds with this method), which is considered to be due to the presence of hemicellulose and other contaminants in the raw pulp and the non-uniformity of the alkali cellulose. However, when the raw material was replaced with regenerated cellulose, filtration was possible with this application, whereas filtration was not possible with the conventional method, and this is thought to be due to the low hemicellulose content in the raw material.

[0066] <Example 3> The viscose produced from cellophane of Example 1 was mixed with industrial viscose. 10 parts of the viscose of Example 1 was mixed with 90 parts of viscose manufactured by Rengo Co., Ltd. (prepared from dissolving pulp by a conventional method) to prepare a mixed viscose (cellulose: 9.7% by mass, sodium hydroxide: 6.2% by mass).

[0067] The viscosity and clogging degree of the obtained viscose were measured in the same manner as in Example 1. The solubility of cellulose was evaluated based on the clogging degree. The results are shown in Table 2.

[0068] <Example 4> The sulfurized cellophane of Example 1 was mixed with the sulfurized pulp. The sulfurized regenerated cellulose sample of Example 1 was mixed with a sulfide prepared from dissolving pulp in a conventional manner so that the mass ratio of regenerated cellulose to native cellulose was 1:9, and then dissolved in an alkaline aqueous solution to prepare viscose (cellulose: 9.8% by mass, sodium hydroxide: 6.1% by mass).

[0069] The viscosity and clogging degree of the obtained viscose were measured in the same manner as in Example 1. The solubility of cellulose was evaluated based on the clogging degree. The results are shown in Table 2.

[0070] <Example 5> The mercerized cellophane of Example 1 was mixed with the mercerized pulp. The mercerized regenerated cellulose sample of Example 1 was mixed with mercerized pulp prepared from dissolving pulp by conventional methods so that the mass ratio of regenerated cellulose to native cellulose was 1:9. 35% by mass of carbon disulfide per mass of cellulose was added and the mixture was sulfurized for 4 hours, after which it was dissolved in an alkaline aqueous solution to prepare viscose (cellulose: 9.8% by mass, sodium hydroxide: 6.1% by mass).

[0071] The viscosity and clogging degree of the obtained viscose were measured in the same manner as in Example 1. The solubility of cellulose was evaluated based on the clogging degree. The results are shown in Table 2.

[0072] <Comparative Example 2> Crushed cellophane mixed with pulp The regenerated cellulose sample and dissolving pulp were mixed so that the mass ratio of regenerated cellulose to native cellulose was 1:9. This mixture was immersed in an 18% by mass aqueous sodium hydroxide solution at 50°C for 1.5 hours to perform mercerization, and then pressed to obtain alkali cellulose (cellulose: 26% by mass, sodium hydroxide: 16% by mass). Carbon disulfide was added to the alkali cellulose to a concentration of 35% by mass per cellulose mass, and sulfurization was carried out for 4 hours. Aqueous sodium hydroxide solution was added to the obtained sulfide, and the mixture was dissolved with stirring at 20°C for 19 hours to prepare viscose (cellulose: 9.6% by mass, sodium hydroxide: 6.0% by mass).

[0073] The viscosity and clogging degree of the obtained viscose were measured in the same manner as in Example 1. The solubility of cellulose was evaluated based on the clogging degree. The results are shown in Table 2.

[0074] <Comparative Example 3> The mercerized cellophane of Comparative Example 1 was mixed with the mercerized pulp. The mercerized regenerated cellulose sample of Comparative Example 1 was mixed with mercerized pulp prepared from dissolving pulp by conventional methods in a mass ratio of regenerated cellulose to natural cellulose of 1:9, and after sulfurization, the mixture was dissolved in an alkaline aqueous solution to prepare viscose (cellulose: 9.6% by mass, sodium hydroxide: 6.0% by mass).

[0075] The viscosity and clogging degree of the obtained viscose were measured in the same manner as in Example 1. The solubility of cellulose was evaluated based on the clogging degree. The results are shown in Table 2.

[0076] [Table 2]

[0077] Examples 3, 4 and 5 have good solubility. In contrast, Comparative Examples 2 and 3, which were subjected to conventional soaking and squeezing, have poor solubility. Example 5 also has lower solubility than Examples 3 and 4. This is thought to be because cellophane, which has a small surface area, is less reactive than pulp in the sulfurization reaction, and sulfurization proceeds unevenly. Separate sulfurization of cellophane and pulp makes the reaction uniform, which is expected to be more preferable in terms of solubility.

[0078] In the present invention, the conditions for obtaining alkali cellulose by mercerizing regenerated cellulose have been optimized, and it has been found that viscose suitable for producing molded bodies can be obtained by mixing it with viscose from wood pulp at that stage or in a sulfurized state, or by mixing it with industrial viscose in a state of viscose dissolved in an alkaline aqueous solution after sulfurization. This reduces the need for dedicated production facilities, allows the effective use of existing facilities, and is also advantageous in terms of energy costs.

Claims

1. An alkali cellulose material containing regenerated cellulose, an alkali and water, which is used to produce viscose by sulfurization with carbon disulfide, the alkali cellulose material having a cellulose concentration of 27 to 40% by mass and an alkali concentration of 8 to 20% by mass.

2. 2. The alkali cellulose material of claim 1, wherein the cellulose component is free of native cellulose.

3. 2. The alkali cellulose material of claim 1, wherein the cellulose component comprises regenerated cellulose.

4. 2. The alkali cellulose material of claim 1, wherein the viscose has a cellulose concentration of 5% by weight or more.

5. 2. The alkali cellulose material of claim 1, wherein the viscose has a clogging factor of 6,000 or less.

6. A mixed alkali cellulose material comprising the alkali cellulose material of claim 1 and an alkali cellulose material for the same purpose produced from a cellulose material other than regenerated cellulose.

7. The sulfide of an alkali cellulose material containing regenerated cellulose, an alkali and water, and having a cellulose concentration of 27 to 40% by mass and an alkali concentration of 8 to 20% by mass, with carbon disulfide.

8. A mixed sulfide of alkali cellulose material with carbon disulfide comprising the sulfide of alkali cellulose material according to claim 7 with carbon disulfide and a sulfide of alkali cellulose material for the same use produced from a cellulose material other than regenerated cellulose with carbon disulfide.

9. Viscose comprises regenerated cellulose, an alkali and water, and comprises a sulfide of an alkali cellulose material having a cellulose concentration of 27-40% by weight and an alkali concentration of 8-20% by weight with carbon disulfide.

10. A mixed viscose comprising the viscose according to claim 9 and a viscose made from a cellulose material other than regenerated cellulose.

11. A method for producing viscose, comprising sulfurizing an alkali cellulose material, the alkali cellulose material comprising regenerated cellulose, an alkali and water, the alkali cellulose material having a cellulose concentration of 27-40% by mass and an alkali concentration of 8-20% by mass, with carbon disulfide.

Citation Information

Patent Citations

  • Method for measuring AE in concrete structure

    JP1987034053A

  • Recycling of artificial cellulose fibers

    JP2018505973A